Humans, other beings and the environment : harurwa (edible stinkbugs) and environmental conservation in Southeastern Zimbabwe - Mawere, Munyaradzi (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2015)
Humans, Other Beings and the Environment is an ethnographic study of the possibilities for the mutual, symbiotic co-existence of human beings, a unique species of forest insects and natural forests. The result of extensive fieldwork conducted over a period of thirteen months, the book highlights the continuum among humans, wild insects and environmental conservation outcomes in a specific environment of southeastern Norumedzo in rural Zimbabwe. In this respect, it describes interactions and relationships between humans, other beings and the natural forests to demonstrate how some aspects of th.
Machine generated contents note: ch. One Setting the Research Agenda: An Introduction -- ch. Two Entering the Fieldwork Site -- ch. Three Harurwa and the Challenge of the Jiri -- ch. Four Personhood, Stories of the Harurwa Origins and Social Networks: Relationalities and Conservation Practices in the Norumedzo -- ch. Five Social Tensions, Village Politics and Natural Resource Conservation in the Norumedzo Communal Area -- ch. Six Harurwa and the Jiri, Social Networks and Management Practices: The Opportunities and Challenges of the Norumedzo Jiri Conservation -- ch. Seven Theoretical Contribution, Evaluation and Conclusion.
This volume is a revision of the author's PhD thesis.
Includes bibliographical references (pages 192-217).
Print version record.
eBooks on EBSCOhost
Keywords: Human-animal relationships -- Zimbabwe -- Masvingo Province; Stinkbugs -- Zimbabwe -- Masvingo Province; Forest conservation -- Zimbabwe -- Masvingo Province; Social & cultural anthropology, ethnography; Physical anthropology; True stories: discovery / historical / scientific; SOCIAL SCIENCE -- Human Geography; Forest conservation; Human-animal relationships; Stinkbugs; Zimbabwe -- Masvingo Province